The four the hidden DNA of Amazon, Apple, Facebook, and Google - Galloway, Scott (New York Portfolio, 2018)
For all that?s been written about the Four over the last two decades, no one has captured their power and staggering success as insightfully as Scott Galloway.
Includes bibliographical references (pages 283-308) and index.
Keywords: Amazon.com (Firm)